Choice experiment performed on the fresh Black Slavonian pig's meat : a preliminary study - Jelić Milković, Sanja (Array, 2021)
Until now, no research has been carried out in Croatia into consumer preferences for a particular agricultural and food product by a choice experiment. Therefore, little data are available about Croatian consumers' preferences for social concerns (sustainability, biodiversity, rural development and animal welfare) with regard to the consumer choice and behavior favoring local pig breeds, in this case the Black Slavonian Pig breed. A survey was the method used to collect the data, and a survey questionnaire was used as an instrument. The survey was performed on a sample of n = 100 Croatian consumers surveyed online using a hypothetical choice experiment. The data were analyzed using the three logit models: a multinomial logit model (MNL), random parameter logit (RPL), and an error component random parameter logit model (RPL-EC) in order to examine the consumers" heterogeneous preferences for fresh ham meat of the Black Slavonian Pig. The results suggest that the Croatian consumers appreciated a darker red fresh pork meat than the one obtained from the Black Slavonian Pig reared outdoors and semi-outdoor. They also prefer a fresh meat bearing a geographical information label, such as the continental Croatia and continental Croatia + PDO, to a fresh meat without a label.